What’s Wrong with Being Global: Perception of Healthiness of Global Food Products - Neciunskas, Paulius (Organizations and Markets in Emerging Economies, 2022)
This research demonstrates that global food products suffer from healthiness bias – a tendency to favor local food products and evaluate them as healthier than equivalent global or foreign food products. The paper extends previous research findings and provides empirical evidence that the perception of the product’s healthiness is a driver of this phenomenon. Results of three between-subject experimental research design studies indicate that global (versus local and foreign) food products are associated with lower perception of healthiness. In turn, such evaluations impact consumers’ buying intentions. Moreover, bias is more pronounced for consumers who perceive themselves as vulnerable to diseases and, conversely, disappears for those who are not vulnerable to diseases. The paper discusses the theoretical and managerial implications of these findings and points toward future research directions.
Keywords: global products; local products; healthiness bias; disease avoidance